2017
DOI: 10.5005/jp-journals-10052-0085
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Pemphigus Vulgaris

Abstract: Pemphigus vulgaris (PV) is a chronic autoimmune blistering disease of the skin and mucous membranes that affects older individuals. The disease rarely affects children and adolescent patients. The first manifestation of PV appears in the oral mucosa in the majority of patients, followed by cutaneous lesions. The diagnosis is based on clinical findings and laboratory analyses, and it is usually treated by the combined administration of corticosteroids and immunosuppressants. Dental specialists must be proficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…1,2 Usually in pemphigus, oral lesions occur before skin lesions. [7][8][9] In contrast, our patient presented with skin lesions which were preceded by oral lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,2 Usually in pemphigus, oral lesions occur before skin lesions. [7][8][9] In contrast, our patient presented with skin lesions which were preceded by oral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…When a patient presents with generalized chronic ulceration in the oral cavity, the differentials to be considered are pemphigus vulgaris, erythema multiforme, acute herpetic gingivostomatitis, bullous impetigo, linear IgA disease, epidermolysis bullosa, cicatricial pemphigoid, bullous pemphigoid and paraneoplastic 7,8 However, especially in an adolescent, the possibility of pemphigus vulgaris, erythema multiforme, acute herpetic gingivostomatitis, and aphthous ulcers need to be considered. 5 In this case presented here due to lack of ulcer-free period the possibility of aphthous ulcers becomes less likely and further, as there are neither clinical features suggestive of infection nor immunodeficiency status acute herpatic gingivostomatitis can also be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before RTX therapy, various drugs were instituted in pediatric PV patients including systemic corticosteroids such as prednisolone and dexamethasone as the primary treatment modality. One study also reported the use of the topical corticosteroid triamcinolone acetonide [ 32 ]. Other immunosuppressants such as azathioprine [ 9 , 28 , 30 , 31 ], cyclosporine [ 24 ], mycophenolate mofetil [ 9 , 30 , 31 ], and intravenous immunoglobulins (IVIG) [ 9 , 11 , 31 ] were also administered.…”
Section: Reviewmentioning
confidence: 99%